The quality of liquid organic fertilizer made from moringa leaf stems as influenced by the concentration of microbes and the duration of fermentation - Paramita, Vilia Darma (INTEK: Jurnal Penelitian, 2023)
Liquid organic fertilizer from moringa leaf stems was produced through a fermentation process. In this study, moringa leaf stems were utilized by adding banana stems and EM4. The use of moringa leaf stems and banana stems in liquid organic fertilizer was expected to enhance macro-nutrients in the soil, such as nitrogen, phosphorus, and pH. The objective of the research was to determine the optimum conditions for producing liquid organic fertilizer. The experimental variables included adding EM4 starter concentrations of 1%, 3%, and 5% (v/v) to the fermentation substrate and fermenting it for 7, 14, and 21 days. The analysis results indicated that the nitrogen, phosphorus, and pH content of the liquid organic fertilizer met the standards. The optimum conditions were achieved during a 14-day fermentation period with a 5% concentration of EM4, resulting in nitrogen content of 10.06%, phosphorus content of 2.05%, and pH level of 7.5.